Програмна система для дистанційної роботи з маніпуляційними процесами muscle-bit - Ковалевич, Б. І. (ХНУРЕ, 2021)
Nowadays interaction with microprocessors becomes easier. One controller has a lot of computation power and with a high level of connectivity it can be a stand-alone endpoint. We can use it to build the distributed software system based on interaction with microcontrollers for remote work with manipulation control. Not all of business can be transferred to remote work, perhaps this system will help to solve the problem. This project focuses on the ability to remotely interact with sophisticated modules and collect data using the mechanical arm. There is also discussion about a few topics: in which way can we build the distributed software system, my way of solving this problem.
Науковий керівник – доц. Лещинський В. О.
Keywords: програмна система; дистанційна робота